Analisis NAS (Network Attached Storage) Berbasis Cloud Sebagai Layanan Infrasturcture As A Service (IAAS) Menggunakan Open Source Nas4free Dan Owncloud - Sasongko, Hariyo; Hadiwandra, T. Yudi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Today, computer systems and networks are an important part of human life. This can be seen with the large number of computer users, such as in offices, companies, factories, or even on campus andin schools. This need has reached a considerable amount. For now, the storage media that we often used to store data is uses physical media such as hard disks and flash disks. NAS (Network AttachedStorage) is one of the solutions to the problem of expensive storage media, because inside the NAS does not require high hardware resources to share files. NAS4FREE is chosen as the operatingsystem of the NAS server, because NAS4FREE is an open source base operating system and NAS4FREE can also be used on various OS platforms, such as Windows, Apple and UNIX. Testingis launched using several parameters, namely access test through smartphone and desktop devices. Then testing NAS4FREE classification files with a file size of 107.80 MB and a total of 9959 filestakes about 9.16 second with a speed of 1088 files/second and the CPU on NAS4FREE servers is 33.33% with an average usage of 13.21%. Furthermore, Memory testing on NAS4FREE servers was945.96 MB from a memory size of 1.03 GB. For the average delay using a formula, a delay of 126.46 ms was obtained, user management testing and file management were also tested in this study.Keywords: NAS4FREE, Storage, NAS, Operating System